Neuropsychological mechanisms of falls in older adults - Liu, Yu; Chan, John S. Y.; Yan, Jin H. (Frontiers in Aging Neuroscience, 2014)
Falls, a common cause of injury among older adults, have become increasingly prevalent. As the world’s population ages, the increase in – and the prevalence of – falls among older people makes this a serious and compelling societal and healthcare issue. Physical weakness is a critical predictor in falling. While considerable research has examined this relationship, comprehensive reviews of neuropsychological predictors of falls have been lacking. In this paper, we examine and discuss current studies of the neuropsychological predictors of falls in older adults, as related to sporting and non-sporting contexts. By integrating the existing evidence, we propose that brain aging is an important precursor of the increased risk of falls in older adults. Brain aging disrupts the neural integrity of motor outputs and reduces neuropsychological abilities. Older adults may shift from unconscious movement control to more conscious or attentive motor control. Increased understanding of the causes of falls will afford opportunities to reduce their incidence, reduce consequent injuries, improve overall well-being and quality of life, and possibly to prolong life.